Effect of Family Harmony on Teenage Delinquency Behavior Tendency - Gultom, Nova Dialusi (Acta Psychologia, 2022)
One of the factors that influence the occurrence of juvenile delinquency behavior is family. The family process that occurs will affect family members in behaving and behaving. A harmonious family will create happiness for all family members while a family that is not harmonious will create unpleasant conditions between family members and this can create a compensatory reaction for adolescents to carry out delinquency behavior. This study aims to determine the effect of family harmony on the tendency of adolescent delinquency behavior. The research subjects were 181 middle-aged adolescents who lived with their parents. The sampling technique used was the cluster technique. The data were collected using two types of scales in the form of a Likert scale. The first scale is the family harmony scale (r = 0.901) and the second scale is the juvenile delinquency behavior scale (r = 0.939). Analysis of research data using simple linear regression analysis which produces a regression equation Y = 149.84 – 0.645 * family harmony. The coefficient of determination produced is 0.477 (R² = 0.477) so that it can be said that family harmony contributes 47.7% effectively to the formation of juvenile delinquency behavior tendencies. The results of additional analysis showed that there were differences in the tendency of juvenile delinquency behavior based on gender (t = 6,800, p = 0.000), where men had a higher tendency for delinquency behavior than women.